Photodetectors: Environmentally Robust Black Phosphorus Nanosheets in Solution: Application for Self‐Powered Photodetector (Adv. Funct. Mater. 18/2017). (May 2017) - Ren, Xiaohui; Li, Zhongjun; Huang, Zongyu; Sang, David; Qiao, Hui; Qi, Xiang; Li, Jianqing; Zhong, Jianxin; Zhang, Han
Abstract : Xiang Qi, Han Zhang, and co‐workers fabricate 2D black phosphorous (BP) nanosheets and successfully apply them as photodetectors in KOH electrodes. As the researchers report in article number1606834, the excellent photoresponse of the environmentally robust sheets can be adjusted via the KOH concentration. The photodetector is a promising building block for optoelectronic devices, while the as‐prepared BP nanosheets can yield 2D BP heterostructures for different applicaitons.